Varnost pacienta in zdravstvenih delavcev : (konferenčni zbornik) / 26. posvet Medicina, pravo in družba, (23.-24. marec 2017, Maribor, Slovenija) - Marina Bajić; Kraljić, Suzana; Reberšek Gorišek, Jelka; Rijavec, Vesna (2017)
Safety of Patients and Health Care Professionals : Conference Proceedings / 26th Conference Medicine, Law & Society. Safety today represents a key factor in the provision of high-quality health care. Hospitals and other medical institutions therefore consider ensuring of the patient's safety, but also of the health professionals, as the main goal and priority of their operation. The concept of safety is multifaceted, interdisciplinary (e.g. it links law and medicine), and may result in both short-term and long-term consequences for patients, health professionals and ultimately also for the entire health system. The provision of safety no longer has a purely national aspect, but also has also gained cross-border and international dimensions, since we live in a time of large-scale mobility of persons and a perpetual flow of information, goods and services. Therefore, it is of the utmost importance to ensure the safety of patients and health professionals in the light of various factors. To achieve this goal, it is necessary to strive for continuous improvement and upgrading of existing key factors and, in this regard, to include all relevant stakeholders in the healthcare sector and, where appropriate, more widely.
Keywords: Law; Medicine; Society